Meditação Shabad Kriya para tratamento da insônia: um ensaio clínico randomizado - Marcus Vinicius Prado da Cruz (2024)
Introduction: Insomnia is today a public health problem in Brazil and around the world. Integrative and complementary mind-body practices including Yoga and Meditation, have been used to improve overall health and quality of life. This study aimed to evaluate the practice of meditation called Shabad Kriya immediately before bedtime and the quality of sleep of people with insomnia. Additionally, a bibliographic review of the literature was carried out analyzing randomized clinical trials whose main outcome was the quality of sleep in patients undergoing Yoga and/or meditation to improve these conditions. Methodology: This is a prospective, randomized, controlled study with two groups. The test group received the meditation intervention using the Shabad Kriya technique and the control group received relaxing reading. The sample size was calculated using the G*Power program and taken as a reference to previous studies using yoga to treat insomnia. Based on this, a minimum sample of 174 individuals (87 in each group) was defined to obtain statistical power of 80% to detect an improvement in the insomnia severity index (IGI) and sleep quality between the initial averages. and after the intervention. The IGI used to screen participants with insomnia, and as a method of evaluating interventions. The collected data were tabulated and subjected to analysis with the aid of the R software. Comparison between the groups was made using parametric and non-parametric tests and the mobility matrix model of the insomnia condition. A p value lower than 0.05 was used for the results to be considered statistically significant. Results: Comparisons between paired groups in the dependent samples, using non-parametric Wilcoxon tests, showed significance (p<0.001) from the beginning of treatment to the end of 8 weeks for the meditation and relaxing reading group, and between the beginning and a month after the end of treatment (p<0.001). Comparisons between independent samples, using the Mann Whitney tests, showed a statistically significant difference (p=0.038) between the mediation and relaxing reading groups, one month after the interventions in favor of the meditation group, revealing a possible cumulative residual effect of this practice. There was no statistical difference between the meditation and relaxing reading groups at the end of the eight weeks of these two interventions. Conclusion: the use of meditation interventions using the Shabad Kriya technique and relaxing reading were effective in reducing IGI. The Shabad Kriya technique proved to be superior to relaxing reading when the groups were compared one month after the intervention ended.